2017
DOI: 10.1080/14756366.2017.1350658
|View full text |Cite
|
Sign up to set email alerts
|

New sulfurated derivatives of cinnamic acids and rosmaricine as inhibitors of STAT3 and NF-κB transcription factors

Abstract: A set of new sulfurated drug hybrids, mainly derived from caffeic and ferulic acids and rosmaricine, has been synthesized and their ability to inhibit both STAT3 and NF-κB transcription factors have been evaluated. Results showed that most of the new hybrid compounds were able to strongly and selectively bind to STAT3, whereas the parent drugs were devoid of this ability at the tested concentrations. Some of them were also able to inhibit the NF-κB transcriptional activity in HCT-116 cell line and inhibited HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…28 The derivatives of cinnamic acid include p-coumaric, and caffeic acids exhibited significant efficacy in terms of preventing osteoclastic activity and promoting osteoblastic activity. 11,17,[29][30][31][32] Besides, one of the most common antioxidant supplements, propolis, is also rich in cinnamic acid content and was reported to block NF-κB and MAPK activation in macrophage cells. 11 Gabriele et al also…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…28 The derivatives of cinnamic acid include p-coumaric, and caffeic acids exhibited significant efficacy in terms of preventing osteoclastic activity and promoting osteoblastic activity. 11,17,[29][30][31][32] Besides, one of the most common antioxidant supplements, propolis, is also rich in cinnamic acid content and was reported to block NF-κB and MAPK activation in macrophage cells. 11 Gabriele et al also…”
Section: Discussionmentioning
confidence: 99%
“…showed inhibition of NF-κB transcription factors with cinnamic acid derivatives. 17 Schink et al reported that cinnamic acid reduced the phosphorylation of Akt and IKB-α along with decreased IL-8 expressions. 33 Decreased levels of pro-inflammatory cytokines TNFα, IL-1β, and IL-18 and neutrophil infiltration and apoptosis in mice were also demonstrated in another study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…STAT homologs in mammals are comprised of six conserved structural domains, as follows: N-domain (ND), coiled-coil, DNA binding, linker, Src homology 2 (SH2), and transcriptional activation domain [ 31 , 32 ]. Under normal physiological conditions, the activation of STATs is strictly regulated, which could regulate cell proliferation, survival and other critical cellular functions by modulating the expression of specific target genes.…”
Section: Resultsmentioning
confidence: 99%